Response to Niklasson's Comment on Lin, et al. (2012): "The Relation between Postural Movement and Bilateral Motor Integration". Issue 2 (October 2014) - Lin, Chin-Kai; Kuo, Bor-Chen; Wu, Huey-Min
In the study of Lin, Wu, Lin, Wu, Wu, Kuo, and Yeung (2012), the relationship between the validity of postural movement and bilateral motor integration in terms of sensory integration theory was examined. Postural movement is the ability to use the antigravity postures required for stabilization of the neck, trunk and upper extremities via muscle co-contractions in the neck and upper extremities, and balance. Niklasson's (2013) comment argued that postural movement should include primitive reflexes in terms of the general abilities approach. Niklasson (2013) focused on the efficacy of the treatment rather than the theoretical frameworks implied in the therapeutic activities. For that purpose Lin, et al . (2012) used sensory integration as the theoretical foundation, and the relationship between postural movement and bilateral motor integration was assessed via empirical data. The result of Lin, et al . (2012) was offered as a theoretical reference for therapeutic activities.